THE EFFECT OF REAP STRATEGY ON READING COMPREHENSION OF THE EIGHT GRADE STUDENTS - Dewi, Ida Ayu Gede Puspita Ratna; Marhaeni, Anak Agung Istri Ngr.; Paramartha, A.A. Gede Yudha (International Journal of Language and Literature, 2019)
The purpose of this study is to investigate whether there was a significant effect of REAP strategy on reading comprehension of the eight grade students in SMP Negeri 3 Tabanan. The design of this study is quasi experiment of post – test only control group design involving 61 students as the sample. The samples were chosen by using random sampling technique. The data was collected through post – test by using multiple choice test. Independent sample test was used to test the hypothesis. The result showed that the main score of experimental group (74.9) was higher than control group (67.3). Inferential statistical analysis’s result (t = .679, df = 59, p<0.05 (0.01)) indicated that there was a significant effect of REAP strategy of students’ reading comprehension of the eight grade students in SMP Negeri 3 Tabanan academic year 201802019. According to Eta Squared formula, the effect size of this research was 0.11 which was considered as moderate effect based on Cohen’s effect size guideline.